2016
DOI: 10.1590/bjpt-rbf.2014.0155
|View full text |Cite
|
Sign up to set email alerts
|

The Glittre-ADL test reflects functional performance measured by physical activities of daily living in patients with chronic obstructive pulmonary disease

Abstract: BackgroundThe Glittre-ADL test (TGlittre) is a valid and reliable test for the evaluation of functional capacity and involves multiple physical activities of daily living (PADL), which are known to be troublesome to patients with Chronic Obstructive Pulmonary Disease (COPD). However, it is still unknown if this test is also able to reflect the functional performance of patients with COPD.ObjectiveTo investigate whether the TGlittre reflects the functional performance of COPD patients and whether the necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
(62 reference statements)
0
19
0
1
Order By: Relevance
“…In addition, the Glittre ADL-test can differentiate between the functional status of healthy individuals and that of patients with COPD 8 . Furthermore, the time to complete the Glittre ADL-test has been shown to correlate with walking and sitting time in COPD patients, as well as with other ADL 13 . Similar physiological responses were found between the Glittre ADL-test and the six-minute walk test (6MWT), oxygen uptake being slightly higher during the Glittre ADL-test 9 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Glittre ADL-test can differentiate between the functional status of healthy individuals and that of patients with COPD 8 . Furthermore, the time to complete the Glittre ADL-test has been shown to correlate with walking and sitting time in COPD patients, as well as with other ADL 13 . Similar physiological responses were found between the Glittre ADL-test and the six-minute walk test (6MWT), oxygen uptake being slightly higher during the Glittre ADL-test 9 …”
Section: Introductionmentioning
confidence: 99%
“…According to results in COPD, the TGlittre induced higher oxygen consumption, but the cardiovascular and ventilatory responses were similar to those observed in the 6MWT. 14 This is the first study investigating the TGlittre applicability in ILD, with a representative sample of several subtypes, demonstrating its reliability and validity. It cannot be ruled out that the sample size may have caused a type II error in some correlation analyses.…”
Section: Discussionmentioning
confidence: 80%
“…According to results in COPD, the TGlittre induced higher oxygen consumption, but the cardiovascular and ventilatory responses were similar to those observed in the 6MWT. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Bendixen et al 12 also found inefficiency in performing tasks involving patients with COPD, and about 90% reported tiredness and more effort in order to perform such activities; this is similar to our study, although the patients with COPD had no depressive symptoms. Functional limitations in activities of daily living may not only be perceived by patients due to the severity of lung disease, because their level of physical activity, which is required for ADL, is hindered by dyspnea 3,34 .…”
Section: Discussionmentioning
confidence: 99%